Effect of kecombrang flower extract (Etlingera elatior) and basil leave extract (Ocimum afrinacum) to the growth of Streptococcus mutans ATCC 35668 and Staphylococcus aureus ATCC 33591 - Tanahboleng, Katharina Devi Permata; Masruhim, Muh. Amir; Daru, Taufan Purwokusumaning (Generasi Biologi Indonesia, 2023)
Utilization of local plants is still not optimal. Experimental research has been carried out in Samarinda City by utilizing Kecombrang Flower (Etlingera elatior) and Basil Leaf (Ocimum afrinacum) extracts which were exposed to Streptococcus mutans ATCC 35668 and Staphylococcus aureus ATCC 33591. The aim of the study was to determine the effect of kecombrang flower extract (Etlingera elatior) , basil leaf extract (Ocimum afrinacum) on the growth of Streptococcus mutans ATCC 35668, and staphylococcus aures ATCC 33591. The research samples were kecombrang flowers ((Etlingera elatior) and basil leaves (Ocimum afrinacum). The research instrument was a measuring tool (ruler). Results Data analysis showed that kecombrang flower extract (Etlingera elatior), basil leaf extract (Ocimum afrinacum) significantly affected the growth of Streptococcus mutans and Staphylococcus aureus ATCC 33591 (p˂0.00).Active chemicals (secondary metabolites, namely tannins present in kecombrang flower extract and extract Basil leaves (Ocimum afrinacum) can inhibit or kill the growth of Streptococcus mutans ATCC 35668 and Staphylococcus aureus. The conclusion is kecombrang flower extract (Etlingera elatior) and basil leaf extract (Ocimum afrinacum) have a significant effect on the growth of Streptococcus mutans ATCC 35668 and Staphylococcus aureus ATCC 33591.